Gospel-Culture Relationship of Traditional Filipino Religion and Catholicism - del Castillo, Fides (The international journal of religion and spirituality in society, 2015)
The early Filipinos had a traditional religion before the Spanish expedition reached the Philippines in the fifteenth century. They have their own set of cultural traditions, beliefs, and practiced a religious system. But the question on why and how did the majority of Filipinos have come to accept the Catholic religion as an alternative to their indigenous religious beliefs is a question asked by many historians and anthropologists. This paper contributes to the discussion on how Christianity developed in the Philippines by drawing out similar constructs between the indigenous religion of the early Filipinos and Christianity. The paper concludes that the lack of tension between the traditional religion of the early Filipinos and Catholicism allowed Christianity to prosper and dominate in the Philippines.